2008
DOI: 10.1074/jbc.m708544200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor ARF Promotes Non-classic Proteasome-independent Polyubiquitination of COMMD1

Abstract: Although the tumor suppressor ARF is generally accepted for its essential role in activating the p53 pathway, its p53-independent function has also been proposed. Here, we report that ARF associates with COMMD1 and promotes Lys 63 -mediated polyubiquitination of COMMD1 in a p53-independent manner. We found that ARF interacts with COMMD1 in vivo. Deletion analysis of ARF suggested that the N-terminal amino acids 15-45 are important for its interaction with COMMD1. In addition, we found that endogenous ARF redis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Alternatively, the presence of COMMD1 in endosomes/MVB may influence the fate of ATP7B by shifting equilibrium from recycling to targeting to multivesicular bodies and lysosomal degradation. The potential role of COMMD1 in membrane protein recycling is supported by the recent observation of K63-linked ubiquitination of COMMD1 (34), which is a modification implicated in targeting the apical membrane proteins into the endosomal recycling pathway (35). The observation that immunofluorescence shows little COMMD1/ATP7B co-localization is consistent with other studies (9) and is likely to reflect a more general role of COMMD1 as a scaffold for various proteins (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, the presence of COMMD1 in endosomes/MVB may influence the fate of ATP7B by shifting equilibrium from recycling to targeting to multivesicular bodies and lysosomal degradation. The potential role of COMMD1 in membrane protein recycling is supported by the recent observation of K63-linked ubiquitination of COMMD1 (34), which is a modification implicated in targeting the apical membrane proteins into the endosomal recycling pathway (35). The observation that immunofluorescence shows little COMMD1/ATP7B co-localization is consistent with other studies (9) and is likely to reflect a more general role of COMMD1 as a scaffold for various proteins (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…7, B and D, lane 6). This observation was consistent with a previous study that showed that COMMD1 was degraded via the proteasomal and not by the lysosomal pathway (54).…”
Section: Atp7b Clusterin and Commd1 Exist In A Complex-co-supporting
confidence: 83%
“…Consistent with the notion that COMMD1 functions in multiple cellular pathways, COMMD1 is ubiquitously expressed and located at different subcellular sites. COMMD1 has been detected in the nucleus (23,32) and in the cytoplasm (33), where it may be associated with intracellular membranes (29,33). In this study, we identified COMMD1 as a novel interaction partner of SOD1, and we show that COMMD1 plays an important role in the maturation of SOD1.…”
mentioning
confidence: 67%